2017
DOI: 10.1159/000479161
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel Promotes Cell Apoptosis in Uterine Leiomyomas

Abstract: Uterine leiomyomas are common clinical gynecological tumors, which are a major health concern for many women. In the current study, we aimed to investigate the effect of paclitaxel (PTX) on uterine leiomyomas. A mouse model of uterine leiomyomas was established by estradiol benzoate, followed by treatment with increasing doses of PTX. PTX showed no dose-limiting toxicity that affected the survival of mice, and was able to restore the apoptosis level of uterus tissues of the model mice to normal levels. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The antitumor effects of PTX have been attributed to defects in mitotic spindle assembly, chromosome segregation, and cell division. Previous studies have found that PTX can induce apoptosis in different cancer cell lines . However, recent studies have found that PTX can also inhibit EMT related proteins, similar to Zn .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antitumor effects of PTX have been attributed to defects in mitotic spindle assembly, chromosome segregation, and cell division. Previous studies have found that PTX can induce apoptosis in different cancer cell lines . However, recent studies have found that PTX can also inhibit EMT related proteins, similar to Zn .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that PTX can induce apoptosis in different cancer cell lines. [22][23][24] However, recent studies have found that PTX can also inhibit EMT related proteins, similar to Zn. 25,26 Therefore, the combination of Zn and PTX may contribute to the prevention of prostate cancer resistance and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Paclitaxel accelerates the formation of microtubules from microtubule dimers and prevents their separation, which induces abnormal mechanical reorganization of the microtubules and inhibits normal cell division. This drug also inhibits the effects of other factors on the microtubule system and, together with the stable binding of microtubule proteins, eventually induces apoptosis ( Liu et al, 2017a ). In clinical applications, paclitaxel has shown good efficacy in treating non-small cell lung cancer ( Hoang et al, 2012 ), breast cancer ( Manhas et al, 2022 ), gastric cancer ( Tu et al, 2022 ), nasopharyngeal cancer ( Xia et al, 2022 ), ovarian cancer ( Kong et al, 2023 )and cervical cancer ( Yasunaga et al, 2022 ), particularly for drug-resistant tumors ( Song et al, 2018 ; Kawiak et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Paclitaxel is used as a first-line treatment for advanced diseases (breast, ovarian, and lung cancers), as monotherapy or combination therapy (3). Numerous phase I and phase II trials have been reported, suggesting the potential effect of paclitaxel in treating advanced gastric cancers (4,5). It inhibits microtubule depolymerization, causes cell cycle arrest at the G 2 /M phase and suppresses tumor growth (6).…”
mentioning
confidence: 99%